Focus Group Discussion on Students Perspective View on COVID-19 and Distance Education - Samia Sarwar, Iram Qamar, Tehreem Mehmood, Shahid Nazeer, Junaid Iqbal, Kosar Aziz, Rizwan Saeed, (Pakistan Journal of Medical & Health Sciences, 2022)
ABSTRACT Introduction: The COVID-19 could be a dangerous widespread that has influenced each angle of life including education. The educational institutes have been closed to avoid the spread of the infection, and they have changed over their system into distance education. Completing the semester there's a have to be address the risky issues within the modern framework to create it for future usage Objectives: 1-To explore the effects of Covid-19 on life style 2- To know the perceptions and suggestions regarding online education in pandemic Material and Methods Study design: Qualitative Settings: Rawalpindi Medical University Duration: Six months i.e. 1st January 2021 to 30th June 2021 Data Collection procedure: It was focus group discussion conducted via Zoom link. There were 15 medical students were selected from all five classes of MBBS randomly after taking informed consent. A variety of issues that were obtained from the discussion were identified. Results: The findings have uncovered that most of the members were influenced by the widespread period contrarily Anxiety, hope less, and fatigue. It is clear from the findings that education process has had its shortcomings instead of its advantages such as need of interaction, and communication which lead the students to segregation, issues about exams, conventional instructive habits, the load of assignments, and time administration. On the other side the advantages regarding flexibility of place and time to learn and comfort in assessment Conclusion: It is evident that the COVID-19 widespread process has influenced the students’ lives adversely. These negative sentiments have not been overcome by the instruction they uncovered all through the period. While, in conventional campus life they would be at the side their companions and teachers and they would overcome the issues together through socializing. Distance education system tried to facilitating teaching. The COVID-19 widespread period ought to be regarded as an opportunity for teachers to consider how to push the distance education framework forward. Within the light of the findings, it would be awesome to create the current distance education practices which we may well are beyond any doubt that long-term executions get a solid premise.